Sterilisasi produk siap saji: Cakalang (Katsuwonus pelamis Linnaeus 1778) dalam Kemasan Retort Pouch: Sterilization of ready-to-eat products: Skipjack tuna (Katsuwonus pelamis Linnaeus 1778) in retort pouch packaging - Elsa Azhari; Muhamad Subroto Aliredjo; Niken Dharmayanti; Agus Heri Purnomo (Jurnal Pengolahan Hasil Perikanan Indonesia, 2023)
An important factor in providing a product is its shelf life. This study aimed to determine the time required for sterilization by considering the damage to the quality of food ingredients due to heating and maintaining product acceptance by consumers. The methodological approach of this research is the sterilization process by experimenting with the retort pressure setting and the materials used: (A) 1.8 bar pressure with 100% skipjack; (B) pressure 1.2 bar with 90% skipjack; (C) pressure 1.2 bar with 70% skipjack; (D) 1.8 bar pressure with 50% skipjack. The maximum temperature is 121,1oC. Additional ingredients used were potatoes and balado (spicy) seasoning. This analysis includes two components: determination of the adequacy of the sterilization process at a lethal rate of 3.5, and observation of quality degradation based on organoleptic changes and Total Plate Count (TPC) after the product is removed from the packaging. The results showed the adequacy of the sterilization process (actual sterilization process temperature and time) for sample A at 121.1oC for 4.8 minutes, sample B at 114.5oC for 4.8 minutes, sample C at 115.4oC for 5.31 minutes and sample D at 124oC for 13.4 minutes. The results show that sample A has the best criteria in addition to a central temperature of 121.1oC and the time it takes is not too long. Further analysis by measuring the organoleptic after the sterilization process showed that sample A had the highest preference level of 8.2. For the best products, TPC analysis was carried out on unpackaged products with different storage times (3, 9, and 12 h), and the results were 2×102, 2×102, and 3×103, indicating that product storage for 12 h still met the SNI standard for the number of fishery products, namely 5x105.